Kurt Georg Kiesinger. “Il cancelliere dimenticato” - Serra, Maurizio (Rivista di studi politici internazionali, 2007)
Kurt Georg Kiesinger (1904-1988) usually referred to as “the forgotten Chancellor”, was in reality a political key-player in the transition in Germany between the reconstruction phase named after Adenauer and Erhard and the wide political action of Brandt, Schmidt and Kohl till the end of the Cold War. An introverted personality with a dubious past in Nazi times, he emerged in his three years of premiership of the so-called “great coalition” (1966-69) as a solid and far-reaching administrator, promoting notably R&T, education and pioneering environmental protection. During his tenure, the FRG started to develop its Ostpolitik, the UK gained entrance into the Community and German presence in the European institutions was effectively enhanced. RÉSUMÉ - Kurt Georg Kiesinger (1904-1988), surnommé “le chancelier oublié”, a été le principal artisan de la transition politique de la RFA entre le centrisme de Konrad Adenauer et de Ludwig Erhard dans l’immédiat après-guerre et l’ouverture aux grands courants de la politique internationale opérée par Brandt, Schmidt et Kohl jusqu’à la fin de la guerre froide. Personnalité complexe au passé chargé, il sut néanmoins interpréter avec patience et ténacité les exigences d’une société moderne notamment dans les secteurs de la recherche, de l’environnement, de l’éducation. C’est pendant le gouvernement de “grande coalition” qu’il présida de 1966 à 1969, que furent jetées les bases de l’Ostpolitik et de la normalisation des relations avec l’Est. Sur le plan européen, il se battit avec conviction et succès pour éliminer le véto français à l’entrée du Royaume-Uni dans la Communauté et pour élever le niveau de la participation allemande dans les institutions communautaires.